Infant vaccination against malaria in Mozambique and in Togo: mapping parents’ willingness to get their children vaccinated - Vera Cruz, Germano (Hum Vaccin Immunother, 2019)
Background: Malaria is one of the most widespread and deadly diseases worldwide and large majority of malaria cases and deaths occurs in Africa. Efforts to develop an effective vaccine against malaria are underway and several vaccine prototypes are on different clinical trial phases. Objective: As many sub-Saharan African countries have shown interest in introducing large-scale infant vaccination against malaria when a definitively approved vaccine will be available, the present study aimed at mapping Mozambican parents’ willingness to get their children vaccinated and comparing the results with findings from a similar study we conducted in Togo (209 participants). Methods: In Mozambique, 227 parents indicated their willingness to get their children vaccinated (using an 11-point scale) against malaria under different conditions varying as a function of the main constructs of health-protective theories: perceived risk of getting malaria, perceived severity of malaria, effectiveness of the vaccine, cost of the vaccine, and neighbors’ attitude toward vaccination. The participant responses were subjected to cluster analysis, ANOVA and Ch(2) test. Results: Six qualitatively different positions were found, which were labeled Cost (12%); Neighbors, Risk, and Cost (28%); Treatment, Risk, and Cost (10%); Always Vaccinate (7%); Risk and Cost (13%); and Risk, Treatment, Effectiveness, and Cost (22%). These positions were associated with participants’ socio-demographic characteristics. Conclusion: A similar variety of parental positions on malaria vaccination was found in Mozambique and in Togo, which suggests that malaria vaccination campaigns in sub-Saharan African countries must be tailored in design and implementation to match the diversity of parents’ needs and views.